2013
DOI: 10.1016/j.devcel.2013.07.002
|View full text |Cite|
|
Sign up to set email alerts
|

A Multifunctional Protein, EWS, Is Essential for Early Brown Fat Lineage Determination

Abstract: Summary A recent surge in obesity has given impetus to better understand the mechanisms of adipogenesis, particularly brown adipose tissue (BAT) due to its potential utilization for anti-obesity therapy. Postnatal brown adipocytes arise from early muscle-progenitors but how brown fat lineage is determined is not completely understood. Here, we show that a multifunctional protein EWS (Ewing Sarcoma) is essential for determining brown fat lineage during development. BATs from Ews-null embryos and newborns are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 48 publications
(65 reference statements)
1
73
0
Order By: Relevance
“…Consistent with this, brown preadipose cells express many muscle-specific genes and the mitochondrial proteome of brown fat and muscle are highly related to one-another (Forner et al, 2009; Timmons et al, 2007). Interestingly, several factors influence muscle versus brown fat cell fate including PRDM16, C/EBP-β, EHMT1, EWS and ZFP516 (Dempersmier et al, 2015; Kajimura et al, 2009; Ohno et al, 2013; Park et al, 2013; Seale et al, 2008) (Fig. 1).…”
Section: Human Batmentioning
confidence: 99%
“…Consistent with this, brown preadipose cells express many muscle-specific genes and the mitochondrial proteome of brown fat and muscle are highly related to one-another (Forner et al, 2009; Timmons et al, 2007). Interestingly, several factors influence muscle versus brown fat cell fate including PRDM16, C/EBP-β, EHMT1, EWS and ZFP516 (Dempersmier et al, 2015; Kajimura et al, 2009; Ohno et al, 2013; Park et al, 2013; Seale et al, 2008) (Fig. 1).…”
Section: Human Batmentioning
confidence: 99%
“…Deletion of Ewing sarcoma gene Ews results in offspring in which BAT fails to differentiate due to the loss of bone morphogenic protein (Bmp)7 transcription. This defective BAT does, however, express myogenic genes ectopically (82).…”
Section: Divergent Origins Of Brown Beige and White Adipose Tissuesmentioning
confidence: 91%
“…These findings led to the discovery of transcriptional regulator Prdm16 (PRD1-BF1-RIZ1 homologous domain-containing 16), which typifies the BAT lineage as opposed to the myogenic lineage, both arising from a myoblast progenitor and distinctly separate from the white adipogenic pathway (101). Additionally, it has been shown that a multifunctional protein, Ewing sarcoma, is essential for determining BAT lineage (82). Deletion of Ewing sarcoma gene Ews results in offspring in which BAT fails to differentiate due to the loss of bone morphogenic protein (Bmp)7 transcription.…”
Section: Divergent Origins Of Brown Beige and White Adipose Tissuesmentioning
confidence: 99%
“…Moreover, YB-1 is essential for Bmp7 expression during brown adipocyte differentiation in vitro . Furthermore, Ewing Sarcoma (EWS), a multifunctional protein that is essential in determining brown fat lineage during development, forms a complex with YB-1, and this complex directly activates Bmp7 transcription to induce brown adipogenesis [11] (Fig. 2).…”
Section: Yb-1 and Ckdmentioning
confidence: 99%
“…Recently, increasing evidence has shown that YB-1 plays a protective role in acute or chronic kidney injury [6, 10]. Furthermore, YB-1 may be involved in the pathogenesis of obesity-related kidney disease (ORKD) [11]. Unfortunately, no comprehensive review of the role of YB-1 in kidney injury is currently available.…”
Section: Introductionmentioning
confidence: 99%